Writing Our Way into the Public Sphere. Issue 10 (October 2018) - Rose, Mike
Background/Context: The article is a reflection of the importance of bringing educational research into the public sphere, with particular emphasis on writing for broader, nonacademic audiences. Purpose: The purpose of the article is to argue for making educational research more accessible to a broader public and to present suggestions for graduate-level writing instruction to do so. Research Design: This article is an analytic essay. Conclusions/Recommendations: I conclude with some thoughts about the ways "public scholarship" benefits both public awareness and research itself and also offer several suggestions as to how the profession can encourage public scholarship.